ANALISIS SISTEM PENGENDALIAN INTERNAL (INTERNAL CONTROL SYSTEM) PADA AKTIVITAS PENERIMAAN KAS DAN PENGELUARAN KAS PADA PERUSAHAAN (STUDI KASUS PADA PT. X) - Andrean Titus (2020)
This study aims to determine the internal control system) on the activity of cash receipts and cash disbursements that exist in the company PT. X, whether the internal control system has been running well or not. The theory used in this research activity is the theory of Mulyadi. And the method used for this research is descriptive qualitative, and use case study approach and also using interpretive paradigms, data analysis techniques used during the research process in the form of interviews, observations and documentation with key informants and also supporting informants. The results of this study are that PT. X still does not meet some elements of internal control, because there are still practices that are not in accordance with literature or theoretical studies. Where, there are still concurrent tasks performed by the accounting and finance (treasurer) and internal audit units in the company and also by accounting. This practice is feared to provide an opportunity for unscrupulous individuals to deviate from company assets or cash, so that it can harm the company. But despite these shortcomings, PT. X already has a good internal control system.